2016
DOI: 10.4149/gpb_2016003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noise stress on cardiovascular system in adult male albino rat: implication of stress hormones, endothelial dysfunction and oxidative stress

Abstract: Abstract. Noise pollution has been realized as an environmental stressor associated with modern life style that affects our health without being consciously aware of it. The present study investigated the effect of acute, chronic intermittent and chronic continuous exposure to noise of intensity 80-100 dB on heart rate and mean systemic arterial blood pressure in rats and the possible underlying mechanisms. Noise stress causes significant increase in heart rate, mean systemic arterial blood pressure as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…Overall, the present systematic review found clear evidence of a relationship between occupational noise exposure and the risk of hypertension. We assess the causality between exposure to occupational noise and the development of hypertension according to Hill [ 76 ], as follows: Mechanistic studies demonstrate an increased excretion of blood pressure-increasing hormones, such as adrenaline and noradrenaline in noise-exposed workers [ 26 , 27 ], and animal studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] support the biological plausibility of the link. Further evidence of a dose-response relationship between the level of occupational noise exposure and risk of hypertension supports the association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the present systematic review found clear evidence of a relationship between occupational noise exposure and the risk of hypertension. We assess the causality between exposure to occupational noise and the development of hypertension according to Hill [ 76 ], as follows: Mechanistic studies demonstrate an increased excretion of blood pressure-increasing hormones, such as adrenaline and noradrenaline in noise-exposed workers [ 26 , 27 ], and animal studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] support the biological plausibility of the link. Further evidence of a dose-response relationship between the level of occupational noise exposure and risk of hypertension supports the association.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal studies report correlations between acute [ 6 , 7 , 8 , 9 ] or chronic noise exposures [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] and an increase of blood pressure. On the other hand, four experimental studies found no association between noise and blood pressure increase [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased release of stress hormones, activation of sympathetic nervous system, increased reactive oxygen species production, endothelial dysfunction, peripheral vasoconstriction, increased peripheral vascular resistance, and increased blood viscosity are among the proposed mechanisms elicited by acute or chronic noise stress leading to detrimental outcomes on the cardiovascular system [7,9,38]. Following this line of investigation, Said and El-Gohary studied the effect of noise in the 80-100-dB range on heart rate and mean systemic arterial blood pressure in adult male albino rats and explored possible underlying mechanisms [39]. They concluded that noise stress has many adverse effects on cardiovascular system through increasing plasma levels of stress hormones, oxidative stress, and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…150 In animal models, chronic exposure to continuous noise (80–100 dB) has been reported to increase heart rate and mean systemic arterial blood pressure, functional changes that were associated with an increase in plasma corticosterone, adrenaline and endothelin-1. 151 Therefore, it is not surprising that exposure to environmental noise has been found to be associated with increased CVD risk in several epidemiological studies. In a recent meta-analysis of 14 studies on the association between road traffic noise and CHD, the pooled estimate of RR was found to be 1.08.…”
Section: The Social Environmentmentioning
confidence: 99%